Assessing the impact of diseases and their control on livestock productivity: The role of quantitative epidemiology - Perry, Brian D.; McDermott, John J. (Cambridge University Press, 1998)
In determining research priorities, as well as in evaluating the relative merits of different disease control options, there is an increasing demand for impact assessment, in order to justify and support research and development investments. In this process, quantitative epidemiology has a significant role to play. This paper first outlines the categories of impacts that diseases have on society and discusses how these can be measured. Using the example of tick-borne infections of livestock, the paper describes five quantitative epidemiological tools that can be used in impact assessment. These are: geographical information systems (GIS) to estimate disease distribution; mathematical models to quantify infection dynamics; observational field studies to link infection status with production loss; statistical models to enhance study design; and spreadsheet models for economic impact assessment. In each category, examples are given of recent studies.